2013
DOI: 10.1371/journal.pone.0056008
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Non-Communicable Disease in Transition Communities in an Asian Megacity: Baseline Findings from a Cohort Study in Karachi, Pakistan

Abstract: BackgroundThe demographic transition in South Asia coupled with unplanned urbanization and lifestyle changes are increasing the burden of non-communicable disease (NCD) where infectious diseases are still highly prevalent. The true magnitude and impact of this double burden of disease, although predicted to be immense, is largely unknown due to the absence of recent, population-based longitudinal data. The present study was designed as a unique ‘Framingham-like’ Pakistan cohort with the objective of measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…2,3 During the last two decades, Asian developing countries have become more vulnerable to this serious public health threat. Although there has been a need for updated population-based data on the prevalence of obesity among adults in Pakistan, few regional studies [13][14][15][16][17] with adults have identified the escalating rates of overweight and obesity. We therefore established such a kind of study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 During the last two decades, Asian developing countries have become more vulnerable to this serious public health threat. Although there has been a need for updated population-based data on the prevalence of obesity among adults in Pakistan, few regional studies [13][14][15][16][17] with adults have identified the escalating rates of overweight and obesity. We therefore established such a kind of study.…”
Section: Discussionmentioning
confidence: 99%
“…Low income countries currently account for 80% of all non-communicable disease including high BP or CVD. The change in diet behavior could partly account for the rise in high BP or CVD [30]. The findings of the study suggest the effects of diet patterns on longitudinal BP change even in a low-income and lean population.…”
Section: Discussionmentioning
confidence: 99%
“…The authors then read the full text of all 29 articles, and excluded studies that were not suitable for this meta-analysis. Eleven articles were excluded because they were the incorrect type of articles, such as reviews and workshop summaries; five articles had the wrong methodology (three included patients who had concurrent infection with other pathogens); one article was a cross-sectional study and did not study the relationship between exposure to HBV and atherosclerosis [15]; one article that considered cerebrovascular disease as an outcome included both ischaemic and haemorrhagic cerebrovascular disease [7]; seven articles had the wrong outcomes (they studied the parameters related to atherosclerosis but did not set a threshold to define atherosclerosis) [4][5][6][16][17][18][19]; and one article was a cohort study, but there was no other cohort study to perform the meta-analysis [11]. Finally, we included five eligible studies for the meta-analysis [8-10, 12, 13].…”
Section: Study Identification and Selectionmentioning
confidence: 99%